Index of the cycle of money - The case of Poland - Challoumis, Constantinos (Research Papers in Economics and Finance, 2022)
This paper assesses to well-establish the theory of the cycle of money works in a real scenario like this of the economic system of Poland. The prior works have revealed the case of Latvia, Serbia, Bulgaria, Greece, Thailand, and Ukraine according to the concept of the theory of cycle of money. The outcomes concede that Poland is over to the average global value. Then, Poland’s results confirm that it is a well-structured economy and can overpass an economic crisis. The applied methodology is in the same line with the scrutiny of the theory, mathematical, statistical, and econometrical results. The current work is significant as declares the strength of Poland’s economy to a potential crisis. The studying period is from 2012 - 2017, which the EU and general Europe counteracted an economic crisis. This is the first published work for Poland according to this theory and belongs to a project that analyzes the cycle of money of multiple countries.